Before Boas : the genesis of ethnography and ethnology in the German Enlightenment - Vermeulen, Han F., 1952- (Critical studies in the history of anthropology., 2015)
"An extensive study of the emergence of ethnology and ethnography, and how theories in Europe and Russia during the eighteenth century experienced a paradigm shift with the work of Franz Boas starting in 1886"--